Recent Experiences in Managing Capital Inflows-Cross-Cutting Themes and Possible Policy Framework : Supplementary Information. (Policy Papers; Policy Paper ;, 2011)
This supplement provides further information on some of the issues covered in Recent Experiences in Managing Capital Inflows-Cross-Cutting Themes and Possible Policy Framework that have been highlighted in staff's informal discussions with Directors. These include the role of supply-side factors behind the surge in capital flows and the nature of the framework pertaining to the use of capital flow management measures (CFMs).